Improvement on Prototype for Mechanism Binding Part in Tempeh Packaging Process - Asnawi Radzuan; Mohd Harun, Dalila (Progress in Engineering Application and Technology, 2024)
Tempeh, a cherished Indonesian food staple, has seen rising demand, necessitating more efficient packaging systems. This study focuses on enhancing tempeh packaging by designing and integrating automated binding mechanisms into existing packaging systems. The objective is threefold: first, to refine the binding parts’ design for automation; second, to develop a miniature model of these parts for incorporation into automated packaging systems; and third, to verify the efficiency and consistency of the binding mechanisms. The project’s flow involves initial research to identify packaging inefficiencies and select the most suitable mechanism for machine operation. An Arduinobased system, incorporating ultrasonic sensors and motors, controls the binding process. The sensor detects the tempeh’s position, triggering the motor to bind the tempeh with a rubber band. The motor’s speed and duration are adjustable, allowing precise control over the binding process. Efficiency testing involved eight trial runs and four design iterations to evaluate the mechanism’s functionality. The data obtained from these tests was crucial in identifying areas for improvement. While this approach proved effective, it acknowledged the potential for testing-related errors and highlighted the necessity of continual refinement through proficiency testing. This study underscores the potential of automated binding mechanisms in enhancing tempeh packaging efficiency and consistency, contributing to meeting the growing demand while reducing labor costs and ensuring reliable quality. The tempeh binding machine project is a game-changer for making tempeh. It uses smart tech to tie soybeans together faster and easier, cutting down on hard work. This machine is super reliable, making sure each soybean bundle is just right. It’s looking promising for big use worldwide, helping all kinds of tempeh makers. This cool invention updates old ways, saving money and making more tempeh. But it still needs some tweaks and tests to make sure it works great for everyone. Overall, it’s a big step toward making tempeh-making better, faster, and more eco-friendly.